Drift Instabilities in Thin Current Sheets Using a Two‐Fluid Model With Pressure Tensor Effects. Issue 5 (22nd May 2019) - Ng, Jonathan; Hakim, Ammar; Juno, J.; Bhattacharjee, A.
Abstract: The integration of kinetic effects in fluid models is important for global simulations of the Earth's magnetosphere. We use a two‐fluid 10‐moment model, which includes the pressure tensor and has been used to study reconnection, to study the drift kink and lower hybrid drift instabilities. Using a nonlocal linear eigenmode analysis, we find that for the kink mode, the 10‐moment model shows good agreement with kinetic calculations with the same closure model used in reconnection simulations, while the electromagnetic and electrostatic lower hybrid instabilities require modeling the effects of the ion resonance using a Landau fluid closure. Comparisons with kinetic simulations and the implications of the results for global magnetospheric simulations are discussed. Key Points: The drift kink and lower hybrid drift instabilities are studied using a 10‐moment fluid model Inclusion of the nongyrotropic pressure tensor improves agreement with kinetic results for the kink mode Ion physics of the lower hybrid drift instability can be reproduced using a nonlocal heat flux closure